2017
DOI: 10.1242/dev.143719
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling enforces cardiac chamber identity in the developing ventricle

Abstract: Atrial and ventricular cardiac chambers behave as distinct subunits with unique morphological, electrophysiological and contractile properties. Despite the importance of chamber-specific features, chamber fate assignments remain relatively plastic, even after differentiation is underway. In zebrafish, Nkx transcription factors are essential for the maintenance of ventricular characteristics, but the signaling pathways that operate upstream of Nkx factors in this context are not well understood. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 55 publications
9
67
1
Order By: Relevance
“…Nonetheless, fgfr1‐dn‐cargo is functional in the LPM descendants, as expression of the FGF target genes etv4 and spry4 (Figs. ) was reduced at 36 hpf in pectoral fin buds when fgfr1‐dn‐cargo was triggered at 10–11 ss (14–15 hpf); and we observed cardiac phenotypes as reported for SU5402 treatment or genetic perturbations (Marques et al, ; de Pater et al, ; Pradhan et al, ; Reifers et al, ) (Fig. C).…”
Section: Discussionsupporting
confidence: 84%
“…Nonetheless, fgfr1‐dn‐cargo is functional in the LPM descendants, as expression of the FGF target genes etv4 and spry4 (Figs. ) was reduced at 36 hpf in pectoral fin buds when fgfr1‐dn‐cargo was triggered at 10–11 ss (14–15 hpf); and we observed cardiac phenotypes as reported for SU5402 treatment or genetic perturbations (Marques et al, ; de Pater et al, ; Pradhan et al, ; Reifers et al, ) (Fig. C).…”
Section: Discussionsupporting
confidence: 84%
“…After priming in the developing LPM, triggering fgfr1-dncargo expression at 20 ss (19 hpf) resulted in disrupted pectoral fins ( Figure 6D-F), while fgfr1-dn-cargo triggered at earlier time points caused no overt pectoral fin defects. Nonetheless, fgfr1-dn-cargo is functional in the LPM descendants, as i) expression of the FGF target genes etv4 and spry4 (Figure 5, Supplementary Figure 2), and less notably dusp6 (Supplementary Figure 3), was reduced at 36 hpf in pectoral fin buds when fgfr1-dn-cargo was triggered at 10-11 ss (14-15 hpf), and ii) we observed cardiac phenotypes as reported for SU5402 treatment or genetic perturbations (de Pater et al, 2009;Marques et al, 2008;Pradhan et al, 2017;Reifers et al, 2000) ( Figure 6C). Together, these observations support an LPM-autonomous requirement for FGF activity during the critical phase of pectoral fin bud outgrowth between 18-28 hpf in zebrafish, when FGF10 and FGF24 are active in the tissue (Fischer et al, 2003;Norton et al, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…However, increasing the dosage of BMP4 weakened the induced expression of SAN-specific markers. [26]. Further studies showed that NKX2-5 is the downstream regulator of the FGF signaling [13,14].…”
Section: Discussionmentioning
confidence: 98%